Alcohol Use During COVID-19 in Adults with Severe Untreated AUD. Issue 3 (3rd July 2022) - Hutchison, Morica; Aldalur, Aileen; Maisto, Stephen A.; Chiang, Andrew; Abar, Beau; Stecker, Tracy; Conner, Kenneth R.
ABSTRACT: Evidence demonstrating increased alcohol use during COVID-19 comes from low- to moderate-alcohol use samples and has yet to use adults with severe but untreated AUD. Using a community sample of adults with severe AUD, this exploratory, cross-sectional study examined associations of COVID-19 alcohol use. Participants were recruited for a phase-II RCT. Only baseline measures, completed prior to randomization, were analyzed in the present study. Key variables were alcohol consumption, COVID-19-related worries and experiences, and qualitative responses of 1) alcohol use and 2) positive changes during COVID-19. At total of 176 pariticpants recruited since COVID-19 were on average 41.4 years old, 49.1% female, and 79% White. Participants drank alcohol nearly 23 of the past 30 days, consumed 7 standard drinks per drinking day, and nearly 90% reported increased alcohol use. More heavy episodic drinking was reported in the first six-months of COVID-19 and more COVID-related concerns in the most recent six-months. Participants reported drinking increased due to "more time on their hands, " but the pandemic also "strengthened relationships." Results affirm an increase in alcohol use during COVID-19 in adults with severe, untreated AUD. Findings underscore the need to understand how alcohol use and pandemic-related circumstances may influence one another for adults with severe AUD.